The Effect of Parental Social Support on Academic Procrastination of Vocational Education Students in Mechanical Engineering at Sultan Ageng Tirtayasa University - Prayuda, Ridzki; Iman, Atep; Ramdani, Sulaeman Deni (The Future of Education Journal, 2025)
This study investigates the extent to which parental social support influences academic procrastination among student of the vocational Mechanical Engineering Education Program at Sultan Ageng Tirtayasa University. Employing a descriptive quantitative approach with purposice sampling, 30 students participated as respondents. Data were collected through questionnaires measuring parental social support and academic procrastination, then analyzed using simple linear regression via SPSS 20. The findings indicate a significant negatice relationship between the two variables, with higher parental support associated with reduced acade,oc procrastination. The study concludes that parental roles-through emotional, appraisal, and informational support-are essential in fostering students academic discipline.